Structure-based de novo design, molecular docking and molecular dynamics of primaquine analogues acting as quinone reductase II inhibitors - Murce, Erika; Cuya-Guizado, Teobaldo Ricardo; Padilla-Chavarria, Helmut Isaac; França, Tanos Celmar Costa; Pimentel, Andre Silva (Journal of molecular graphics & modelling, 2015)
Primaquine is a traditional antimalarial drug with low parasitic resistance and generally good acceptance at higher doses, which has been used for over 60 years in malaria treatment. However, several limitations related to its hematotoxicity have been reported. It is believed that this toxicity comes from the hydroxylation of the C-5 and C-6 positions of its 8-aminoquinoline ring before binding to the molecular target: the quinone reductase II (NQO2) human protein. In this study we propose primaquine derivatives, with substitution at position C-6 of the 8-aminoquinoline ring, planned to have better binding to NQO2, compared to primaquine, but with a reduced toxicity related to the C-5 position being possible to be oxidized. On this sense the proposed analogues were suggested in order to reduce or inhibit hydroxylation and further oxidation to hemotoxic metabolites. Five C-6 substituted primaquine analogues were selected by de novo design and further submitted to docking and molecular dynamics simulations. Our results suggest that all analogues bind better to NQO2 than primaquine and may become better antimalarials. However, the analogues 3 and 4 are predicted to have a better activity/toxicity balance.
Keywords: Molecular Docking Simulation; katalytická doména; simulace molekulového dockingu; Protein Binding; vodíková vazba; sekundární struktura proteinů; Humans; Quinone reductase II; termodynamika; Catalytic Domain; Quinone Reductases; primachin; Toxicity; Hydrogen Bonding; chinonreduktasy; inhibitory enzymů; Primaquine; vazba proteinů; Protein Structure, Secondary; Molecular Dynamics Simulation; lidé; Thermodynamics; simulace molekulární dynamiky; Enzyme Inhibitors; de novo design; Malaria